PERSEPSI TUAN GURU, GURU DAN SANTRI PONDOK PESANTREN DI KALIMANTAN SELATAN TENTANG JIHAD - Barni, Mahyudin (Khazanah: Jurnal Studi Islam dan Humaniora, 2008)
For these days/lately the word jihad get the popularity and related to some bomb action in Indonesia. Some actors inspected by the government officer, actually have a pesantren (Islamic Boarding School Community) background. This fact peeping out stigmatism that pesantren was a place to train terrorists. Research has been conducted to three oldest pesantren in South Kalimantan. The result dhowed that ruan guru, guru (teacher), dan santri (pupil at pesantren) have a perception in the widw meaning. Not only discussed about war and assasination but also for fighting, fight a bad desire that lead someone to negative and desteructive deeds. Jihad as war is part of Jihad fi sabilillah, and jihad needs some term and condition and it expecially for people who has an obiligation to do jihad. Law of jihad in moslims perception is fardlu 'ain and also fardlu kifayah